1991
DOI: 10.1002/ar.1092290309
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of “Tissue‐Specific” antigens in the developing human heart and skeletal muscle. II. An immunohistochemical analysis of myosin heavy chain isoform expression patterns in the embryonic heart

Abstract: The spatial distribution of alpha- and beta-myosin heavy chain isoforms (MHCs) was investigated immunohistochemically in the embryonic human heart between the 4th and the 8th week of development. The development of the overall MHC isoform expression pattern can be outlined as follows: (1) In all stages examined, beta-MHC is the predominant isoform in the ventricles and outflow tract (OFT), while alpha-MHC is the main isoform in the atria. In addition, alpha-MHC is also expressed in the ventricles at stage 14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 52 publications
1
79
0
Order By: Relevance
“…In the fetus, it can be identified as a ring of nodelike cells in the right atrium just above the tricuspid valve, which later disappears. 13,33,34 These accessory myocardial AV connections appear to correspond to the presumed multiple AV nodes and pathways originally reported by Kent and reviewed by Anderson et al 35 The relationship of right-sided accessory myocardial AV connections with the RAVR bundle could explain the decremental properties seen in some of the right-sided APs. 36 Within the developing AVN, small myocardial extensions can be identified that cross the annulus fibrosus and connect the developing AVN with the ventricular septal myocardium.…”
Section: Hahurij Et Al Accessory Pathways In Developing Human Hearts mentioning
confidence: 57%
“…In the fetus, it can be identified as a ring of nodelike cells in the right atrium just above the tricuspid valve, which later disappears. 13,33,34 These accessory myocardial AV connections appear to correspond to the presumed multiple AV nodes and pathways originally reported by Kent and reviewed by Anderson et al 35 The relationship of right-sided accessory myocardial AV connections with the RAVR bundle could explain the decremental properties seen in some of the right-sided APs. 36 Within the developing AVN, small myocardial extensions can be identified that cross the annulus fibrosus and connect the developing AVN with the ventricular septal myocardium.…”
Section: Hahurij Et Al Accessory Pathways In Developing Human Hearts mentioning
confidence: 57%
“…Most of the images of human and murine specimens used in the illustrations of this review were generated in the context of studies published previously (26,27,31,37,38,(40)(41)(42)(43). Some of the scanning electron microscope (SEM) images are from the collection of late Tomas Pexieder.…”
Section: Methodsmentioning
confidence: 99%
“…Contributions of the major atrioventricular cushions to valvuloseptal morphogenesis in the human heart. These panels show two serial sections of a human heart at ϳ6 wk of development stained for the presence of atrial MHC (A) and ventricular MHC (B) as described before (42). A: this is how the mesenchymal tissues of the two major cushions and the mesenchymal cap on the IAS have fused to form the mesenchymal "crux" of the heart.…”
Section: Valvuloseptal Developmentmentioning
confidence: 99%
“…The expression of regulatory genes has been detected as early as the earliest observable morphological changes in the fetal murine heart (17). Considerable work done previously has established that the normal development of a septated four-chambered heart from a tubular heart is controlled by the normal expression of musclespecific genes and their regulators (18)(19)(20)(21). Cardiac Troponin I (eTn!…”
mentioning
confidence: 99%
“…Cardiac Troponin I (eTn! ), cardiac troponin T2 (eTnT2), myosin light chain (MLC), myosin heavy chain (MHC) and actin regulate muscle contraction and relaxation and the expression of these genes is regulated by various factors including cardiac ankyrin repeat protein, fibroblast growth factor receptor 1, cardiac ryanodine receptor 2 (RyR2) and NKX2.5 (18)(19)(20)(21).…”
mentioning
confidence: 99%